KERJA SAMA INDONESIA - AUSTRALIA MELALUI PROGRAM MAMPU - Fayzah Anggana Abhirama; Ika Riswanti Putranti; Marten Hanura (Journal of International Relations, 2022)
Empowerment of women and gender equality is still major concern. This issue is still difficult to overcome due to the lack of public awareness about the importance of this issue in Indonesia. Seeing this, Australia, which has a higher awareness of women, invites cooperation with Indonesia through the MAMPU (Maju Perempuan for Poverty Reduction) Program. The collaboration aims to provide women with access to essential services and proper rights. By using liberal feminist theory and the concept of bilateral cooperation, this study has the main argument that the running of the capable program (2012-2020) has been running according to these theories and concepts. The findings of this study are that MAMPU Program has fulfilled liberal feminist theory by making women psychologically aware that they have rights and opportunities which also resulted in several legal changes in Indonesia regarding women, with this Indonesia-Australia cooperation has also run according to the concept of cooperation. bilateral because the response from both countries to the MAMPU Program was very good.